Aktivitas Fraksi Air Kulit Batang Mahoni (Swietenia macrophylla King.) Dan Studi In Silico Senyawa Kimia Penghambat Enzim α-Glukosidase - Arini Khaerunnisa; Ratna Djamil; Lilik Sulastri; Partomuan Simanjuntak (Jurnal Fitofarmaka Indonesia, 2022)
Inhibition of the α-glucosidase can be used as antidiabetic therapy because it can reduce postprandial blood sugar levels. The stem bark of mahogany (Swietenia macrophylla King.) have properties as inhibitors of enzyme α-glucosidase. The purpose of this study was to determine the active compound of mahogany stem bark againstα-glucosidase enzyme in vitro and in silico. 96% ethanol extract of mahogany stem bark was partitioned with n-hexane, ethyl acetate and water. Testing of inhibition of α-glucosidase enzyme work done with substrate p-nitrophenyl-α-D-glucopyranoside. The water fraction was separated on silica gel column chromatography (SiO2 : dichloromethane-methanol = 10 : 1 ~ 1 : 1 and methanol).Molecular docking using AutoDock 4.2.6 was performed to predict the binding modes of α-glucosidase enzyme with chemical compound from water subfraction of stem bark mahogany. The results showed that water fraction of stem bark mahogany have antidiabetic activity with IC50 value of 1.51 µg/mL. Fraction Fr-1 gave an inhibition of 83.61 ± 1.11 %. Fr-1 contains chemical compound catechin, evodionol and swietenitin K. In silico study showed that catechin and evodionol free energy value (ΔG) -6.98 and -6.25 Kcal/mol and inhibition constanta (Ki) 7.61 and 26.18 µM.